AN ELECTRONIC EXCEL-CALCULATOR FOR CALCULATING DENTAL CROWN VOLUMES - Bulbuk, O. I.; Mazurenko, V. V.; Rozhko, M. M.; Bulbuk, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Previous studies have found that with increasing volume of hard tissues defect, the sensitivity of the restored structure to the physical and mechanical restoration characteristics is increasing too. Since existing volume determination techniques cannot be use in a clinical setting, this gives reason to consider the problem of volume determination dental hard tissue defects extremely important, and this research-relevant. Aims of research. Develop and evaluate the possibility of using methods to determine dental crown volumes and volumes of defects in hard tooth tissue. Materials and methods of research. For determination of crown volumes and defect volumes of hard tooth tissues for each group of teeth were used appropriate geometric models. Together with the built models, were performed the mathematical calculations to calculate their linear dimensions. Results of the research. We have developed and substantiated the feasibility of using an electronic Excel calculator to calculate dental crown volumes in clinical settings. Conclusions. Using our electronic Excel calculator to calculate tooth crown volumes and methods for determining the volume of dental hard tissue defects, in clinical settings we can objectify the diagnostic process in the presence of dental hard tissue defects.